The Law Enforcement of Illegal Fishing in the Perspective of UNCLOS 1982: The Case of Illegal Fishing in the North Natuna Sea - Yordan Gunawan; Muhammad Nur Rifqi Amirullah; Muhammad Rafi Abdussalam; Vensky Ghaniiyyu Putri Permana (Jurnal Cita Hukum, 2022)
The potential for illegal fishing in Indonesia's marine areas is tremendous, especially in Indonesia's exclusive economic zone, particularly in the North Natuna marine area. Following the rampant illegal fishing activities, policies on preventing and eradicating illegal fishing in Indonesia are constantly debated both in theory and implementation. Illegal fishing activities are not only a problem for Indonesia but also a cross-border problem because the perpetrators come from across countries. Therefore the handling of this problem must be cross-border, and implementation of international law is necessary. By using normative legal research, the paper analyzed law enforcement of illegal fishing by referring to UNCLOS as the basis of international maritime law to obtain legal certainty in illegal fishing in the Indonesian exclusive economic zone (EEZ), especially in the North Natuna sea area. According to Article 73 paragraph 1 UNCLOS 1982, Indonesia can take action against perpetrators of illegal fishing by using its own legal regulations because illegal fishing can interfere with the management rights of Indonesia's marine natural resources.Keywords: Illegal Fishing, Indonesian Exclusive Economic Zone, UNCLOS AbstrakPotensi illegal fishing di wilayah laut Indonesia sangat besar, terutama di zona ekonomi eksklusif Indonesia, khususnya di wilayah laut Natuna Utara. Menyusul maraknya aktivitas illegal fishing, kebijakan pencegahan dan pemberantasan illegal fishing di Indonesia tetap menimbulkan permasalahan yang diperdebatkan baik secara teori maupun implementasinya. Kegiatan illegal fishing tidak hanya menjadi masalah bagi Indonesia, tetapi juga menjadi masalah lintas batas karena pelakunya berasal dari berbagai negara, oleh karena itu penanganan masalah ini harus dilakukan secara lintas batas sehingga diperlukan penerapan hukum internasional. Dengan menggunakan penelitian hukum normatif, makalah ini menganalisis penegakan hukum illegal fishing dengan mengacu pada UNCLOS sebagai dasar hukum maritim internasional untuk memperoleh kepastian hukum dalam tindak pidana illegal fishing di Zona Ekonomi Eksklusif Indonesia (ZEE), khususnya di laut Natuna Utara. wilayah laut. Hasil penelitian menunjukkan bahwa menurut Pasal 73 ayat 1 UNCLOS 1982, Indonesia dapat menindak pelaku illegal fishing dengan menggunakan peraturan hukumnya sendiri, karena illegal fishing dapat mengganggu hak pengelolaan sumber daya alam laut Indonesia.Kata Kunci: Illegal Fishing, Zona Ekonomi Eksklusif Indonesia, UNCLOS